2020
DOI: 10.1080/20008198.2020.1766770
|View full text |Cite
|
Sign up to set email alerts
|

A profile analysis of post-traumatic stress disorder and depressive symptoms among Chinese Shidu parents

Abstract: Background: Due to the one-child policy implemented in China, most families have only one child. When parents experience the death of their only child, these parents receive the label 'Shidu parents'. Shidu is a major public health issue in China. However, the patterns of post-traumatic stress disorder (PTSD) and depressive symptoms that are present in this population remain unclear. Objective: This study aims to identify profiles of PTSD and depressive symptoms among Shidu parents and to explore the predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
(107 reference statements)
2
18
1
Order By: Relevance
“…First, this study found a negative association between age and depressive symptoms. This result is inconsistent with some studies (Wang et al, 2015;Zhang & Jia, 2020b) but consistent with an existing study (Eli et al, 2020). A possible explanation is that younger parents may have more ambitions and plans, and the death of their only child subverts their expectations (Zhou et al, 2020).…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…First, this study found a negative association between age and depressive symptoms. This result is inconsistent with some studies (Wang et al, 2015;Zhang & Jia, 2020b) but consistent with an existing study (Eli et al, 2020). A possible explanation is that younger parents may have more ambitions and plans, and the death of their only child subverts their expectations (Zhou et al, 2020).…”
Section: Discussioncontrasting
confidence: 78%
“…A possible explanation is that younger parents may have more ambitions and plans, and the death of their only child subverts their expectations (Zhou et al, 2020). In addition, with increasing age, parents have likely experienced more negative events and thus may have more psychological energy to cope with traumatic events (Eli et al, 2020). Compared with elderly people, young people, who typically experience high pressure from work and family, are often neglected by society and perceive less social support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a meta‐analytic review found that time since trauma was a significant predictor of lower depression and higher positive affect (Helgeson et al., 2006). However, some recent studies found no significant effect of time since trauma (Eli et al., 2020; Shigemoto & Robitschek, 2018), confirmed inconsistent results (Shigemoto et al., 2017), and failed to examine the effect of time since trauma on transitions in the severity of trauma‐related symptoms over time (Read et al., 2016), highlighting researchers' inability to control for time passed. Therefore, in line with these studies which suggest controlling for the amount of time elapsed since traumatic experience (Frazier et al., 2001; Horesh et al., 2011; Shigemoto et al., 2017), we included time since trauma as a covariate.…”
Section: Introductionmentioning
confidence: 98%